RANCANGAN PIT MUARA TIGA BESAR SELATAN BULAN JUNI TAHUN 2015 UNIT PENAMBANGAN TANJUNG ENIM PT BUKIT ASAM (PERSERO) TBK SUMATERA SELATAN - Riandy Kurniawan; Dedi Yulhendra; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2015)
PT Bukit Asam (Persero) Tbk is an Indonesia-based company primarily engaged in coal mining industry. Methods used in open pit such as conventional and continuous mining. This conventional method is conducted by using backhoe and dump truck while for continuous mining used Bucket Wheel Excavator (BWE) and Conveyor. In January 2015, Tambang Muara Tiga Besar Selatan used conventional method such as backhoe and truck. In an effort to increase coal recovery, it is necessary to do broadening area in Tambang Muara Tiga Besar Selatan in order to get more company’s profit. PT Bukit Asam (Persero) Tbk therefore plans to widen Tambang Muara Tiga Besar area for short term in June 2015. This research is conducted to make open pit design, calculate volume of burden and coal, disposal design, and also design mine haulage roads. Based on the result of analysis and calculation that has been done, elevation of pit design is amount of 62 mdpl to 0 mdpl. The total volume of burden is 1.500.000 BCM and tonnage of coal is 375.000 tons derived. The stripping ratio value is 4:1. The disposal area consist of two sections including first priority and second priority. The distance between mining front with disposal area is 1,97 Km. The width of haulage roads for two strips which appropriate with The American Association of State Highway and Transportation Officials (AASHTO) is 30 meters, including trench and dike.